(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
The aim of this study was to evaluate the level of satisfaction of pharmaceutical services and to determine the socioeconomic profile of public pharmacy clients. This is a cross-sectional observational study using a quantitative approach. The sample was calculated from the monthly number of patients seen in pharmacies and was stratified for each pharmacy. Data were analysed using SPSS 11.5 software and by observing the simple relative frequencies for qualitative variables. For the quantitative variables, the analysis of variance (ANOVA) and post-hoc Fisher tests were performed. Data are expressed as mean ± standard deviation (SD). The results show that, in general, patients at "Farmácias cidadãs" are satisfied with the services. However, when stratified, we found that the greatest satisfaction was related only to structural and organizational aspects, while the pharmaceutical services are unsatisfactory. When relating satisfaction to the socioeconomic characteristics, a difference between waiting time (39.07 ± 19.53), attendance by pharmacist (8.91 ± 5.14) and education was observed. It is concluded that users are satisfied with the services of state "Farmácias cidadãs" of Espírito Santo, but there should be improvements in relation to pharmaceutical services and the interpersonal relationships between health professionals and users of the public health system in Brazil.